The Influence of Organizational Culture and Job Satisfaction on Employee Performance at the National Narcotics Agency of South Sumatera Province - Hisar Siallagan; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti Publisher, 2026)
The objectives of this study are as follows: To analyze the influence of organizational culture on employee performance, To analyze the influence of job satisfaction on employee performance and To analyze the influence of organizational culture and job satisfaction simultaneously on employee performance at the National Narcotics Agency of South Sumatra Province. Organizational Culture (X₁) has a significant influence on Employee Performance (Y). The results of the partial test (t test) show that the calculated t value is greater than the t table at a significance level of 5%, Job Satisfaction (X₂) has a significant effect on Employee Performance (Y). The results of the partial test show that job satisfaction has a very strong influence on employee performance and culture. Organization (X₁) and Job Satisfaction (X₂) simultaneously have a positive and significant effect on Employee Performance (Y). The results of the simultaneous test (F test) show that both independent variables together have a significant effect on employee performance at the South Sumatra Provincial BNN. The contribution of Organizational Culture and Job Satisfaction to Employee Performance is relatively strong.